Design and Construction of a Mechatronic Reactor for the Growth of Thin Films by the Dip Coating Technique (2014)
The design and construction of an automated mechatronic system for the growth of thin films by the dip coating technique is presented. The system consists of a substrate-holder, which performs vertical movements between two adjustable positions. The movem